Benefits on pain and mental health of manual therapy for idiopathic scoliosis: A meta-analysis - Ren, Jun; Kong, Lingjun; Wu, Zhiwei; Zhou, Xin; Huang, Qian; He, Tianxiang; Fang, Min (Frontiers in Endocrinology, 2022)
Background Idiopathic scoliosis (IS) is a common spinal disorder. Although several studies have reported the benefits of manual therapy for patients with IS in improving pain, anxiety, depression, and spinal disorders, the efficacy of manual therapy in the management of IS remain controversial. Therefore, this review was conducted to assess effects of manual therapy in the management of IS, primarily on pain and mental health of the patients and secondarily on their spinal disorders. Methods Six electronic databases were searched for randomized controlled trials of manual therapy in the management of IS. The methodological quality of the included studies was assessed using the Physiotherapy Evidence Database (PEDro) Scale. The meta-analysis was conducted depending on different outcomes and control therapies using Review Manager version 5.3 software. Results Seventeen studies were included in the present review. The PEDro scores of the included studies ranged from 5-7 points. The aggregated results indicated that Tuina (a traditional Chinese manipulation technique) had valuable improvement effects on pain (standardized mean difference (SMD), 0.92; 95% confidence interval (CI), 0.59 to 1.25; P<0.00001), negative emotions (SMD, 0.82; 95% CI, 0.51 to 1.13; P<0.00001), and disability (SMD, 1.29; 95% CI, 0.39 to 2.19; P=0.005). For the radiographic outcomes including the Cobb angle and vertebral rotation, Tuina, especially when combined with other conservative therapies, showed potential complementary effects for patients with IS. Conclusions Tuina, as a complementary and alternative therapy, should be considered for the effective management of patients with IS, especially for the improvement of their pain and mental health. More randomized controlled trials are recommended to validate the current evidence.